RANCANG BANGUN APLIKASI BELADIRI INDONESIA (TARUNG DERAJAT KOTA TANGERANG) BERBASIS ANDROID - Muhammad Rendy Nurhakiki; Niki Ratama (Journal of Research and Publication Innovation, 2024)
This research aims to design and build an Android-based Tarung Derajat martial arts application. Based on a survey conducted, many participants have difficulty in organizing training time due to busy schedules, family responsibilities, and far training locations. To overcome these obstacles, a martial arts application was developed with features such as training schedules, video tutorials, and registration. The research method used is the Multimedia Development Life Cycle (MDLC). The MDLC method was chosen due to its systematic approach in the development of multimedia applications, which includes six main stages: concept, design, material collection, creation, testing, and distribution. This application is designed to assist Tarung Derajat practitioners in organizing training schedules, accessing video tutorials, and registering for classes more efficiently. The results showed that this application is able to overcome various obstacles that are often faced by participants, such as time constraints and distance to the training ground. The user survey shows that most users are satisfied with the features provided, although there are some technical issues that need to be improved. This application is expected to be an effective solution to increase participation and quality of Tarung Derajat training in Tangerang City.